Characterizing some photophysical, photochemical and photobiological properties of photosensitizing anthraquinones - Comini, Laura Raquel (2007)
Some photophysical, photochemical and photobiological properties of nine anthraquinones (AQs) isolated from a phototoxic plant, Heterophyllaea pustulata, were studied. The photosensitized generation of superoxide anion radical (O2−) and singlet molecular oxygen (1O2) by three of the nine AQs, namely heterophylline, pustuline and 5,5′-bisoranjidiol was evaluated. Whereas the O2− production (Type I photosensitization mechanism) was examined in vitro using human leukocyte suspensions and measuring the reduction of NBT, the 1O2 generation (Type II photosensitization mechanism) was studied in an organic solvent through the measurement of the quantum yield of 1O2 (ϕΔ). It was established that these three AQs possess photosensitizing properties as do the other AQ derivatives present in this vegetable species, soranjidiol, soranjidiol 1-methyl ether, rubiadin, rubiadin 1-methyl ether, damnacanthal and damnacanthol, acting both by Type I and Type II mechanisms. Furthermore, nordamnacanthal, a species synthesized in the laboratory from one of the natural AQs, showed the highest production of 1O2. The ability of natural AQs to deactivate the 1O2 generated during the photosensitization process as well as their fluorescence (as competitive mechanisms to the generation of ROS) was studied.